2011
DOI: 10.1016/j.topol.2010.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Hasse diagrams and orbit class spaces

Abstract: Let X be a topological space and G be a group of homeomorphisms of X. LetG be an equivalence relation on X defined by xG y if the closure of the G-orbit of x is equal to the closure of the G-orbit of y. The quotient space X/G is called the orbit class space and is endowed with the natural order inherited from the inclusion order of the closure of the classes, so that, if such a space is finite, one can associate with it a Hasse diagram. We show that the converse is also true: any finite Hasse diagram can be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The spaces of leaves Y of foliations often appear as spaces of orbits of flows and more generally of group actions and play an important role in the understanding the dynamics of that actions, e.g. [5,15,4,7,10,2,3] and others. The usual difficulty arising at once when we pass from the manifold X to the space of leaves Y is that Y is usually non-Hausdorff.…”
Section: Introductionmentioning
confidence: 99%
“…The spaces of leaves Y of foliations often appear as spaces of orbits of flows and more generally of group actions and play an important role in the understanding the dynamics of that actions, e.g. [5,15,4,7,10,2,3] and others. The usual difficulty arising at once when we pass from the manifold X to the space of leaves Y is that Y is usually non-Hausdorff.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the Conley-Morse graphs are implemented as a computer software CHomP (Computational Homology Project software) [2], and there are several relative works for analyzing dynamical systems using algorithms [14,20,22]. The finite realizability of the orbit class spaces is studied [7,8]. Therefore the question of how to reduce dynamical systems into finite topological invariants is essential from a theoretical and application point of view.…”
Section: Introductionmentioning
confidence: 99%
“…By [3], any connected finite poset can be realized by the singular part of the leaf class space of a transversally oriented codimension one C 1 -foliation on a closed oriented three manifold. In [4], Bonatti et al showed that any finite connected poset can be realized by the orbit class space of a finitely generated group of homeomorphisms of a compact connected topological space. They also state the question of whether any finite Hasse diagram can be realized on a compact manifold.…”
Section: Introductionmentioning
confidence: 99%